Research on Risk Sensitivity of Submerged Floating Tunnel Based on Analytic Hierarchy Process. (2016) - Shuping, Jiang; Qinxi, Li; Jianjun, Li; Gengren, Cao; Xiang, Chen
Abstract: The hierarchical structure model of risks of floating tunnel is built under the sea area conditions in Qiongzhou Strait in combination with the work characteristics in early stage and the overall construction process of floating tunnel. The judgment matrix introduced into the analytic hierarchy process analyzes the relationships between different hierarchical factors for quantitative analysis of their index weight values by A.L.saaty's ratio scale method. The weight values of various main risk factors of floating tunnel are calculated and sequenced, and the risk control measures are proposed. This paper mainly deals with the quantitative research problems in project risk analysis of floating tunnel to provide a reference for decision makers.